Assessment of Serum Enzymatic Antioxidant Levels in Patients with Recurrent Aphthous Stomatitis: A Case Control Study. (10th December 2014) - Gupta, Ishita; Shetti, Arvind; Keluskar, Vaishali; Bagewadi, Anjana
Abstract : Background and Aim. Recurrent aphthous stomatitis (RAS) is a common oral mucosal disorder characterized by recurrent, painful oral aphthae. Despite extensive research, the exact etiology of RAS remains elusive. Recently oxidant-antioxidant imbalance of the body has been implicated in the pathogenesis of recurrent aphthous stomatitis. Thus, the aim of the study was to evaluate the enzymatic antioxidant levels in patients with recurrent aphthous stomatitis. Materials and Methods. The serum levels of superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) were measured in 30 patients with recurrent aphthous stomatitis and compared to the control group, which included 30 healthy subjects. Student's t -test was performed for statistical evaluation. Results. The mean levels of superoxide dismutase (130.2 ± 15.94 U/mL) and glutathione peroxidase (3527.93 ± 488.32 U/L) were found to be significantly lower in study group as compared to control group (211.9 ± 20.93 U/mL, 8860.93 ± 1105.31 U/L, resp.) (P = 0.000 ) while level of catalase in study group was significantly higher when compared to control group (10981.00 ± 1018.07 U/mL versus 9764.00 ± 1621.19 U/mL) (P = 0.000 ). Conclusion. Enzymatic antioxidant system is impaired in recurrent aphthous stomatitis patients and seems to play a crucial role in its pathogenesis.